Fuel efficiency and emissions reduction of hydroxy added gasoline fuel using HydroBoost technology. (1st May 2023) - Sherman, Gregory; Singh, Amit Pratap
Abstract: In the present work, using the HydroBoost technology, performance and emission characteristics of HHO added Gasoline is investigated. HydroBoost technology offers longevity to cell and increases the efficiency as it requires less power to break the bonds of water. Achieving good emission characteristics using HydroBoost technology is still unexplored. In the present work, following the EPA protocols, a comprehensive analysis of Total Hydrocarbon (THC), Methane (CH4 ), NOx, CO2, MPG emissions in four phases is performed. It is shown that harmful gas emissions are reduced in HHO added Gasoline in comparison to only Gasoline fuel. The stoichiometric air-fuel mixture has been achieved in the present work. BSFC (Brake Specific Fuel Consumption) is reduced by up to 11% and the overall emissions of HHO added gasoline are reduced by up to 13% for CO2, up to 72% for Total Hydrocarbons, up to 69% for Methane, up to 48% for NOx in relation to bare Gasoline fuel. The present technology enables Hydroxy gas to be produced on board the IC vehicle without creating an undesirable amount of parasitic loss or hazard, which can be immediately deployed to lower both BSFC and emissions including greenhouse gasses such as CO2 . Highlights: The electrolyzer with catalytic agent and a non-corrosive electrolyte helps in longer life of the system. Hydroxy gas is produced on board without creating an undesirable parasitic loss. Hydroxy gas can be immediately deployed to lower BSFC greenhouse gas emissions. Comparable emission reduction using new electrolyzer technology.